Teaching morphology through advertising: word formation in practice - Hundarenko Olena; Гундаренко Олена (Видавництво «Код», 2025)
Резюме. У статті досліджується, як процеси словотворення функціонують як лінгвістичні інструменти в рекламі, зокрема на платформах соціальних мереж, таких як Facebook, Instagram та TikTok. Спираючись на теоретичні основи морфології та її роль у підтримці життєздатності мови, у статті наголошується, що креативне найменування, слогани та афіксація можуть посилити вплив та запам’ятовуваність рекламних повідомлень.

Abstract. The article explores how word formation processes function as linguistic tools in advertising, particularly on social media platforms such as Facebook, Instagram, and TikTok. Drawing on theoretical foundations of morphology and its role in sustaining language vitality, the article emphasizes that creative naming, slogans, and affixation can enhance the impact and memorability of advertising messages. The empirical research analyzed 60 randomly selected advertisements to determine which word formation strategies appear most frequently. Three research questions guided the study: the most common process; the platform most associated with creative affixation; the platform primarily using blending. Findings confirmed that compounding was the dominant strategy across platforms, Instagram showed isolated but not common use of creative affixation, and TikTok relied more heavily on blending than Instagram. The study concludes that morphological analysis provides valuable insights into the mechanisms of advertising language, offering both marketing students and linguistics students practical perspectives on language creativity, vocabulary expansion, and advertising effectiveness.
Викладання морфології через рекламу: процеси слівоотворення на практиці
Весь випуск: https://sites.google.com/uica.education/nayka/%D0%BD%D0%B0%D1%83%D0%BA%D0%BE%D0%B2%D1%96-%D0%B7%D0%B0%D0%BF%D0%B8%D1%81%D0%BA%D0%B8-16?authuser=0
Keywords: morphology; word formation; advertising; compounding; blending; social media; branding; linguistics; marketing